Lebanon's consociational model, Christian parties and the struggle for political power in post-2005 period. Issue 4 (1st October 2016) - Assi, Abbas
ABSTRACT: In contrast to the expectations of the Christian parties in Lebanon, the Syrian military withdrawal from the country in 2005 did not mark a turning point to strengthen their political roles after several years of marginalization. Instead, their clash of interests left adverse implications for their behaviour, which undermined their ability to advance their interests and the interests of their community in the consociational system. This article argues that three main factors impacted upon their political behaviour: (1) intra sectarian conflicts; (2) inter sectarian conflicts; and (3) external factors (external alliances and regional developments). The impact of those three factors on their behaviour weakened their ability to reach compromises over, for instance, the formulation of a new electoral law that improves the Christian voters' influence on election results, and the presidential elections. The article employs the consociational model as an analytical framework to explain the factors that influence the behaviour of Lebanon's political parties.